Recrystallization behaviour and tensile properties of Al-added medium-Mn-steel at different deformation-annealing conditions. Issue 17 (22nd November 2019) - Sarkar, Arnab; Sanyal, Souriddha; Bandyopadhyay, T. K.; Mandal, Sumantra
Abstract : The role of recrystallisation on structure–property relationship in Al-added medium-Mn steel was investigated at different stages of thermo-mechanical processing comprising of hot forging (HF), hot rolling (HR), cold rolling (CR) and intermediate annealing. The CR-annealed specimens have exhibited faster recrystallisation kinetics than HF-annealed and HR-annealed conditions, as reflected by the higher Avrami exponent (∼1.28) and requirement of minimum annealing temperature-time (1073K-50 min) for complete recrystallisation. The specimen cold rolled and annealed at 1073 K for 3 min (CR-1073K-3 min annealed) has exhibited excellent tensile properties owing to the co-existence of deformed and recrystallised grains. Further, the refinement of ferrite grains, lower austenite aspect ratio and higher volume fraction of γ -fibre of ferrite phase are responsible for better strength–ductility combination in the CR-1073K-3 min annealed specimen. This paper is part of a Thematic Issue on Medium Manganese Steels.